(untitled) (BIOPROSPEK: Jurnal Ilmiah Biologi, 2015)
Explorative descriptive research that has been implemented in paddy-fields at Sasak jalan aim to understand diversity and structure of the community an insect active in the surface of the ground. Insects was collected by pitfall trap method.The result showed, there were 7 ordo, 14 famili and 18 genus of insects in the paddy fields sasak jalan. The diversity of the average ranged from 0.78-0.84. Index of uniformity in each paddy field ranged between 0.66-0,75 with the highest uniformity index was located on the land of the zone I to the value of 0.75. Index dominance in each land, averaging around between 0.18-0.23.